SAP for modeling the deformation of aerial cables in high voltage substations - Oviedo, Hector (2021)
The installation of cables for connection between electrical substation equipment are designed considering loads due to short circuit, own weight, wind, among others, however, they omit additional conditions depending on the final installation or exclude loads, such as those present in high-rise areas. seismic activity, aspects that would complement the cable deformation calculation, on the other hand, the design effort is usually disconnected in 3D models, since they only use anchor points and “splines” to define their trajectory. Knowing the approximate deformation of the cable is important for verifying electrical safety distances, minimizing possible inconveniences in the construction phase. This document presents the integration of various load models for cables, in a finite element representation with SAP2000, including final installation conditions and seismic loads according to IEEE 1527, guaranteeing connection stability, electrical safety distances and equipment integrity. Additionally, the deformation results are connected with an application developed in Dynamo-Python to complement the BIM model in Revit. The methodology is validated according to connection cases documented by the Pacific Earthquake Engineering Research Center (PEER), which records deformation measurements for cables used in electrical substations under different load and installation scenarios. With the proposed integration, expected deformations are obtained at low displacements, presenting a better trajectory adjustment and stress calculation according to those reported by PEER, however, for high displacements, representative differences are obtained in the measured efforts, an aspect to be improved.